Generation and Application of X−ray Pulses on a Terawatt Laser System - Nazarov, M. M.; Garmatina, A. A.; Mitrofanov, A. V.; Sidorov-Biryukov, D. A.; Scheglov, P. A.; Chashchin, M. V.; Potemkin, F. V.; Gordienko, V. M.; Zheltikov, A. M.; Panchenko, V. Ya.
Currently, the Kurchatov Laser−Synchrotron Complex is conducting research on the interaction of powerful femtosecond laser radiation with matter. The purpose of these studies is to develop new techniques and approaches for the characterization of high−temperature plasma, X−rays and particle acceleration, which can be the basis for the work planned within the framework of the synchrotron−neutron project. Laser−driven X−ray production, electron acceleration, nuclear fusion, ultrafast structural dynamics of nanoparticles in intense laser fields remains an active research topic, aimed at generating advanced controllable sources.
Keywords: Physics